Citrullinated fibrinogen detected as a soluble citrullinated autoantigen in rheumatoid arthritis synovial fluids. Issue 8 (31st January 2006) - Takizawa, Y; Suzuki, A; Sawada, T; Ohsaka, M; Inoue, T; Yamada, R; Yamamoto, K
Abstract : Background: Anti-citrullinated protein antibodies (ACPA) are specifically and frequently detected in sera of patients with rheumatoid arthritis (RA). Citrullinated fibrin or fibrinogen is a candidate autoantigen of such antibodies. Objective: To investigate the presence of citrullinated fibrinogen (cFBG) in the plasma or synovial fluid of patients with RA and control patients, and to determine cFBG levels and their relationship with serum markers for RA if it is present. Methods: A sandwich enzyme linked immunosorbent assay (ELISA) to measure cFBG was established using monoclonal antibodies cF16.1 and cF252.1, generated by immunising mice with R16Cit and R252Cit, the fibrinogen Aα chain derived sequences with citrulline at position 16 and 252, respectively, and the presence of cFBG was further investigated with immunoprecipitation-western blotting. Results: Positive signals were detected in 11/15 RA synovial fluids (RASFs), but not in osteoarthritis synovial fluids or RA plasma with sandwich ELISA for cFBG using cF16.1 and an anti-modified citrulline (AMC) antibody. The presence of cFBG in RASFs was confirmed by immunoprecipitation-western blotting. Furthermore, most RA sera strongly reacted against R16Cit. No relationship was seen between RASF cFBG levels and C reactive protein or anti-cyclic citrullinated peptide antibody levels of the paired sera. Conclusion: cFBG is detected as a soluble citrullinated autoantigen in RASFs and may therefore be a genuine candidate antigen for ACPA in patients with RA.